Collectivism-Based Servant Leadership in Indonesian Schools: A Qualitative Case Study of Humanistic Principal Leadership - Ajeng Nandarah Falenciah; Ainur Rifqi; Kaniati Amalia; Amrozi Khamidi; Agustin Hanivia Cindy; Ruguang Zhou; Hamdan Said (Program Studi Manajemen Pendidikan, 2026)
Rigid bureaucratic cultures in schools may weaken teachers’ professional agency and emotional well-being. This study examines how servant leadership practiced by a school principal contributes to a humanistic work environment in an Indonesian junior secondary school. Using a descriptive qualitative design, the study was conducted at SMP Negeri 3 Waru Sidoarjo, East Java, from July to December 2025. Data were collected through participant observation, semi-structured interviews, and documentation involving 12 participants: one principal, one vice-principal, and ten senior teachers. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings show that active listening, humility, emotional support, and participatory problem-solving helped reduce hierarchical distance, strengthen teachers perceived psychological safety, and encourage more open communication in responding to administrative and curriculum-related challenges. This study proposes the Collectivism-Based Servant Leadership Model, or KPBK, by integrating servant leadership with gotong royong, musyawarah, and Ing Ngarsa Sung Tuladha. It also identifies Double-Loop Empowerment as a qualitative mechanism linking principal support, teacher empowerment, and humanistic teacher-student interaction. The findings suggest that school reform requires not only policy mandates and technical training, but also humanistic human resource governance.